Autoclave pre-treatment of foliage – Effects of temperature, residence time and water content on solid biofuel properties. (June 2021) - Kulbeik, Tim; Scherzinger, Marvin; Höfer, Isabel; Kaltschmitt, Martin
Abstract: Foliage is a biogenic material occurring outside the tropical areas typically in autumn. This material is mostly not used for the production of energy because foliage is often characterized by a very high moisture and ash content as well as adhering impurities. Cleaning and drying are very energy-intensive; i.e. the additional energy used for drying is often in no relation to the possible energy yield. In such cases, heat-induced autoclave pre-treatment could be used to improve the solid biofuel properties of the foliage with regard to a subsequent energetic utilization. Here the effects of temperature, residence time and initial water content during autoclave pre-treatment were determined for foliage. The results show that such an autoclave pre-treatment can significantly improve higher heating value by 15 %, grindability, drying behaviour and concurrently reduces moisture content up to 30 wt% and equilibrium moisture content over 40 wt%. Thereby, the investigated effects can only insignificantly reduce the amount of inorganic components and should be separated before autoclave pre-treatment. The optimum operating conditions identified in this study also indicate that temperatures of 170 °C, at residence times of 3 h and an initial water content of the foliage of 50 wt% lead to an improvement of the solid biofuel properties. Graphical abstract: Image 1 Highlights: Autoclave pre-treatment improves higher heating value of foliage by 15%. Moisture content of foliage could reduce by autoclave pre-treatment up to 30 wt%. Grindability of foliage is improved by autoclave pre-treatment. Equilibrium moisture content is reduced by autoclave pre-treatment over 40 wt%. Best results were achieved at 170 °C temperature and 3 h residence time.